If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-3)=(4x-12)
We move all terms to the left:
2(x-3)-((4x-12))=0
We multiply parentheses
2x-((4x-12))-6=0
We calculate terms in parentheses: -((4x-12)), so:We get rid of parentheses
(4x-12)
We get rid of parentheses
4x-12
Back to the equation:
-(4x-12)
2x-4x+12-6=0
We add all the numbers together, and all the variables
-2x+6=0
We move all terms containing x to the left, all other terms to the right
-2x=-6
x=-6/-2
x=+3
| X=(2x+90) | | 15+3x=8x-4 | | 3(x+4)-2(2+2x)=3(x-6x+10+12) | | x÷16.7=-0.7 | | x+4.5=-3.9 | | 3x-15=8x+2-9 | | 19n=13-7+n | | 798=3*n+47 | | 22-4x=12+6x | | x²-2,4x+1,44=0 | | -y/7=-51 | | 6x+12=8x-10-9x | | 4x-6=5x+6-x | | 6.3j–20=16 | | -v/6=-38 | | 3x+68=2x+116 | | 3y+2y-76=3y+11 | | 100=-2x^2+32x | | 4z2=144 | | 3x+7−x=21 | | 3x+7-x=2 | | -9x+81=3(x+63) | | 4c+3=-29 | | 16x+470=21x | | 7+y/3=-5 | | 37x=470 | | -5x-1=x-7 | | 21x+16=470 | | 2(4w-3)=42 | | 3(x+1)=7(x-2)=-3 | | x/4=4+-7 | | 12x+96=-3(x-47) |